OPTIMALISASI PEMANFAATAN MINERAL FOSFOR DALAM MEMBENTUK KESEHATAN FISIK ANAK USIA DINI MELALUI REEDUKASI KELUARGA - Sandey Tantra Paramitha (Gladi : Jurnal Ilmu Keolahragaan, 2018)
The development of early childhood physical health largely determined by levels of phosphorus contained in the body, due to be the second largest item after the calcium in the human body, problems become obstacles in developing family knowledge about the importance of the content of phosphorus in the development of early childhood body i.e. environmental conditions is lacking support and there is no massive support from the Ministry of Health important about phosphorus for the growth of early childhood. This research uses descriptive method which aims to describe, illustrate and analyze events in field data collection techniques, using interviews, observation and documentation, as well as using the techniques of data analysis the presentation of data, data reduction and withdrawal of the conclusion. The results obtained show that the society have less knowledge about the importance of phosphorus for early childhood growth, hence the need for the development of the knowledge society on the importance of phosphorous for growth in early childhood, it due to the excess or deficiency of phosphorus will not impact the tub for the body.